Third grade success : - James, Amy (Jossey-Bass, 2005)
Knowledge Essentials is a remarkable series that will benefit children of all abilities and learning styles. Amy James has taken a close look at curriculum standards and testing around the country and developed simple and creative activities that support what’s being taught at each grade level, while remaining sensitive to the fact that children learn at different rates and in different ways. I highly recommend it for all parents who want to make a difference in their children’s education